Stromal cell-mediated glycolytic switch in CLL cells involves Notch-c-Myc signaling - Jitschin, Regina; Zenz, Thorsten (Blood, 2015)
It is well established that the stromal niche exerts a protective effect on chronic lymphocytic leukemia (CLL) cells, thereby also affecting their drug sensitivity. One hallmark of malignant cells is metabolic reprogramming, which is mostly represented by a glycolytic shift known as the Warburg effect. Because treatment resistance can be linked to metabolic alterations, we investigated whether bone marrow stromal cells impact the bioenergetics of primary CLL cells. In fact, stromal contact led to an increase of aerobic glycolysis and the cells’ overall glycolytic capacity accompanied by an increased glucose uptake, expression of glucose transporter, and glycolytic enzymes. Activation of Notch signaling and of its direct transcriptional target c-Myc contributed to this metabolic switch. Based on these observations, CLL cells’ acquired increased glucose dependency as well as Notch-c-Myc signaling could be therapeutically exploited in an effort to overcome stroma-mediated drug resistance.
Gesehen am 20.07.2017